Altruistic concern: how racial ideologies explain racial differences in concerns for Black victims of crime and the police - Drakulich, Kevin M. (Journal of ethnicity in criminal justice, 2024)
We explore how concerned Americans are about the risk of violence faced by Black Americans. Using a 2022 American National Election Studies (ANES) survey, we compare concern for Black Americans as the victims of crime versus the police. We find White Americans to be the least concerned about both kinds of victimization, Black Americans the most concerned, and Latinx Americans in between. Interestingly, White Americans expressed significantly less concern about Black Americans being victimized by the police than by civilians. People’s racial ideologies play the largest role in explaining the average differences in concern between people with different racial identifications.